Epidemiology of quid usage and its possible association with the occurrence of oral mucosal lesions - Sultan A. Almalki; Inderjit M. Gowdar; Manoj Vengal; Sugandha Arya (Frontiers in Oral Health)
BackgroundChewing tobacco consumption has become a major public health issue in India. The incidence of oral cancer is increasing in India, especially among young adults.AimThe objective of this study was to ascertain the prevalence of chewing tobacco consumption and its association with the occurrence of oral mucosal lesions.MethodsA cross-sectional survey was conducted among 1,209 patients who reported to the Department of Oral Medicine and Radiology at Vyas Dental College, Jodhpur. A structured questionnaire was used to collect information on patients’ personal information such as demographic details, tobacco use, and other adverse habits. A single calibrated investigator performed a clinical examination of lesions on the oral mucosa, and the diagnosis was further validated.ResultsThe majority of the participants were men (81.8%) in the age range of 26–35 years. A habit of chewing a combination of tobacco and areca nut (48.2%) was more prevalent. More than 36% of the participants consumed tobacco in a processed form (90%), at least four times a day. It was observed was 25% of the participants were suffering from tobacco pouch keratosis.ConclusionChewing tobacco was significantly associated with the development of oral mucosal lesions, particularly among men and those belonging to lower socio-economic groups. Along with targeted public health interventions on tobacco cessation, it is essential to change the cultural norms associated with the habit of chewing tobacco and implement strict chewing tobacco control laws in the community and workplaces.